Ikonografi Hindu Abad VIII-XII M di Kabupaten Gianyar, Bangli, dan Buleleng: Analisis Bentuk, Fungsi, dan Makna - I Wayan Srijaya; Kadek Dedy Prawirajaya R; Coleta Palupi Titasari; A. A. Gde Bagus; I Nyoman Rema (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
Iconography is the study of the art of sculpture. The statue is a symbol of God or the embodiment of a deceased public figure. In Indonesia in general and Bali in particular, the tradition of making statues has a long history, from the time of farming to the days of the influence of Hindu and Buddhist civilization. During the Hindu and Buddhist era, the development of statues with Hindu and Buddhist motifs was developed. This research is focused on Hindu-style statues found in Gianyar, Bangli, and Buleleng Regencies. Hindu iconographic research aims to obtain the historical pictures of the arts of the statues, their forms, functions, and meanings in people's lives. The results show that Hindu iconography in Bali has various forms, with different functions from the original functions. Likewise, the meanings depend on the community that makes meanings in the present context.